Ethic-legal ideas in Kyiv-Mohyla academy in the 18th century - V.V. Semykras (Ukrainian Cultural Studies, 2019)
The ethics in the lecture courses of the Kyiv-Mohyla Academy was divided into theoretical and practical parts. The former dealt with the substantiation of a person’s place in the world, considered problems of the meaning of life, free will, a degree of a person’s responsibility for their actions. The latter pointed to ways and means to determine a destiny, achieve happiness, and developed education system according to the perception of a perfect person. Theophan Prokopovych, professor and rector of the Academy, considered a necessary condition for happiness to obtain a certain level of material well-being since poverty and deprivation are not compatible with happiness. He linked the achievements of this with conscientious work, which he considered to be a duty towards himself, his family, society, and the state. He recognized the benefit as the basis of work along with usefulness, which he considered to be close to virtue in terms of significance, thus giving her a positive moral evaluation. Achievement of happiness, according to Theophan Prokopovych, is possible if a person сomply with natural, moral, civil and God’s laws. Natural law makes a person realize the need for work and determines they inclination to a certain kind of it. However, a person must understand what kind of work they are inclined to; this requires the study of their bodily and spiritual needs, that is, self-knowledge. Having known themselves and having discovered the ability for a certain type of labour in themselves, a person works for themselves, their family, society, state. Thus a person obeys moral and civil laws. Introduction to the philosophical course of the section of ethics, though not obligatory for all professors, was at that time necessitated by the desire to rethink the system of human relations in the new historical conditions of Ukraine of the first half of the eighteenth century. human. Ethics becomes an important tool for educating a new person, forming a free personality. Professors do not simply comment and promote moral standards accepted in Christian culture, but seek to study and analyze the authoritative ethical teachings of ancient and European thinkers, trying to give practical guidance on improving man and the moral regulation of society in his time. This tendency was significantly developed and improved by the student of Kyiv-Mohyla Academy, Grigory Skovoroda.